La musique du paysage - Furnelle, Vincent (Uliège Library, 2015)
The landscape originally responds to the awakening of our senses. Before we can even study a site, before we can project our experience, our memories or historical references, we are present with our whole body. The places we travel through invade us; their music overwhelms us. The landscape comes to us at the same time that we lose ourselves in it. We welcome it as it offers itself. Aesthetic moment, in the first sense, that of receptivity. This sensitive meeting is the source of multiple subsequent readings (environmental, patrimonial, economic, sociological, functional...). Its language is that of the landscape itself, inescapable for those who will make it their vocation. However, we often ignore this first discovery; we lack the words to express it. This book intends to let the strings of the landscape vibrate within us, to let its openings, its rhythms, its grain and its lights emerge to all our senses. Our mute experience of places seeks the word.